2005
DOI: 10.1007/s00268-004-7732-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Lymphatic Mapping and Sentinel Node Biopsies for Early‐stage Gastric Cancer: The Cause of False Negativity

Abstract: Sentinel node (SN) biopsies might be useful for performing minimally invasive surgery without interrupting surgical curability. This study examined the cause of false negativity during laparoscopic lymphatic mapping and SN biopsies for early-stage gastric cancer. Thirty-seven patients with gastric cancer (preoperative stage T1-2 or N0) who underwent laparoscopic lymph node mapping and SN biopsies between March 2001 and June 2004 were enrolled in this study. The tracer, patent blue and technecium-99m-labeled ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 15 publications
0
38
1
Order By: Relevance
“…This finding implies the lymphatic system of the stomach is diverse and multidirectional and that skip metastasis frequently occurs [9,10]. Tonouchi et al [26] conducted a literature review to determines the cause of SNB false-negativity in gastric cancer, and concluded that the most common cause was lymphatic occlusion due to massive lymph node metastasis; other identified causes were injection failure, pathologic failure, and intraoperative misses. In the second trial of the present study, clinicopathologically T2 tumors larger than 4 cm tended to be false-negatives, which suggests lymph node metastasis occurs in an unpredictable directional manner, and the possibility of lymphatic obstruction [18].…”
Section: Discussionmentioning
confidence: 95%
“…This finding implies the lymphatic system of the stomach is diverse and multidirectional and that skip metastasis frequently occurs [9,10]. Tonouchi et al [26] conducted a literature review to determines the cause of SNB false-negativity in gastric cancer, and concluded that the most common cause was lymphatic occlusion due to massive lymph node metastasis; other identified causes were injection failure, pathologic failure, and intraoperative misses. In the second trial of the present study, clinicopathologically T2 tumors larger than 4 cm tended to be false-negatives, which suggests lymph node metastasis occurs in an unpredictable directional manner, and the possibility of lymphatic obstruction [18].…”
Section: Discussionmentioning
confidence: 95%
“…Tonouchi et al reported a false-negative case with a metastatic lymph node in the right paracardial area (Station 1), which was in the same lymphatic basin as an SN [22]. They found that the radioactive metastatic lymph node had been missed due to the shinethrough effect.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 91%
“…The necessity of SB dissection is demonstrated by recent publications, especially those concerning laparoscopic SN biopsy in EGC [22][23][24]. Tonouchi et al reported a false-negative case with a metastatic lymph node in the right paracardial area (Station 1), which was in the same lymphatic basin as an SN [22].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 93%
“…The most commonly used tracers for sentinel node mapping are vital dyes, which are detected by visual inspection, and radioisotopes conjugated with colloid particles, which are detected by gamma probes yielding audible signals [4][5][6][7]. In gastric cancer, low sensitivity and rapid dispersion of vital dyes, as well as the need for strict radiohazard-proof protocols and the invisibility of radioisotopes, have been recognized as limitations [8].…”
Section: Introductionmentioning
confidence: 99%